Are people with chronic diseases interested in using telehealth?: a cross-sectional postal survey - Edwards, Louisa; Thomas, Clare; Gregory, Alison; Yardley, Lucy; O'Cathain, Alicia; Montgomery, Alan A.; Salisbury, Chris (Journal of Medical Internet Research, 2014)
Background